2018
DOI: 10.1016/j.jaut.2018.05.010
|View full text |Cite
|
Sign up to set email alerts
|

11 Beta-hydroxysteroid dehydrogenase type 1 regulates synovitis, joint destruction, and systemic bone loss in chronic polyarthritis

Abstract: ObjectiveIn rheumatoid arthritis, the enzyme 11 beta-hydroxysteroid dehydrogenase type 1 (11β-HSD1) is highly expressed at sites of inflammation, where it converts inactive glucocorticoids (GC) to their active counterparts. In conditions of GC excess it has been shown to be a critical regulator of muscle wasting and bone loss. Here we examine the contribution of 11β-HSD1 to the pathology of persistent chronic inflammatory disease.MethodsTo determine the contribution of 11β-HSD1 to joint inflammation, destructi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 39 publications
1
37
0
Order By: Relevance
“…11β-HSD1 KO animals with global 11β-HSD1 deletion were crossed with TNF-tg animals to generate TNF-tg 11βKO animals as previously described. 8 Mesenchymal 11β-HSD1 KO animals were generated by crossing flx/flx-HSD11B1 mice with Twist2-cre mice to generate 11βHSD1flx/flx/Twist2cre animals, which were paired with TNF-tg animals to produce TNFtg 11βHSD1flx/flx/Twist2cre (TNF-tg 11βflx/tw2cre ). [9][10][11] Myeloid targeted 11β-HSD1 KO animals were generated by crossing flx/flx-HSD11B1 mice with LysM-cre mice to generate 11βHSD1flx/ flx/LysMcre animals, which were paired with TNF-tg animals to produce TNF-tg 11βHSD1flx/flx/LysMcre (TNF-tg 11βflx/LysMcre ).…”
Section: Targeted Deletion Of 11β-hsd1mentioning
confidence: 99%
“…11β-HSD1 KO animals with global 11β-HSD1 deletion were crossed with TNF-tg animals to generate TNF-tg 11βKO animals as previously described. 8 Mesenchymal 11β-HSD1 KO animals were generated by crossing flx/flx-HSD11B1 mice with Twist2-cre mice to generate 11βHSD1flx/flx/Twist2cre animals, which were paired with TNF-tg animals to produce TNFtg 11βHSD1flx/flx/Twist2cre (TNF-tg 11βflx/tw2cre ). [9][10][11] Myeloid targeted 11β-HSD1 KO animals were generated by crossing flx/flx-HSD11B1 mice with LysM-cre mice to generate 11βHSD1flx/ flx/LysMcre animals, which were paired with TNF-tg animals to produce TNF-tg 11βHSD1flx/flx/LysMcre (TNF-tg 11βflx/LysMcre ).…”
Section: Targeted Deletion Of 11β-hsd1mentioning
confidence: 99%
“…Mice defective in 11β-HSD1 develop exaggerated joint inflammation in acute and chronic model of arthritis. 6,7 11β-HSD1 activity within macrophages appears to be critical in restraining inflammation in these models. 8 It would be interesting to know whether the responses seen by Koenen et al with dexamethasone are similar using glucocorticoids that are regulated by 11β-HSD1 such as those typically used to treat patients with RA.…”
Section: Unravelling How Glucocorticoids Work In Rheumatoid Arthritismentioning
confidence: 95%
“…Further analysis revealed that while B-cell numbers remained unchanged, there was a significant increase in CD3 + , CD4 + , and CD8 + T-cells, pro-inflammatory M1 macrophages and neutrophils in TNF-tg 11βKO arthritic mice compared to TNF-tg mice. 226 Collectively, these studies suggest that global endogenous GC signaling, when enhanced by increased 11β-HSD1 activity, has predominately antiinflammatory effects in the joint (Table 2). Furthermore, to mechanistically determine whether GR dimerization is required for producing the anti-inflammatory effects of GCs in arthritis, GR dim mice have been utilized in both AIA and K/BxN STA mouse models.…”
Section: Endogenous Glucocorticoidsmentioning
confidence: 98%